Logics of war : the use of force and the problem of mediation - Feiler, Therese, 1982- (London : T&T Clark, 2021)
The modern ethics of war is a field of disparate, competing voices based on often unexplored theological and metaphysical assumptions. Therese Feiler approaches them from the borderline area between systematics, philosophical theology and religious studies. With reference to G. W. F. Hegel's and other like-minded thinkers' 'theo-logic' that negotiates Christ's mediation and immanent dialectics, Feiler identifies the logic and problem of mediation as the core concern of political ethics. Feiler unites five representative authors from now disparate strands of contemporary just war ethics, testing whether they offer a meaningful possibility of mediation and subsequent reconciliation: a sovereign realist, a cosmopolitan idealist, a rationalist individualist, an idealist Christian ethicist, and finally, an evangelical theologian. Opening the just war debate for comparative critical engagement, Feiler creates a fascinating study that locates a 'dynamic point' at which faithful, free political action can be wrestled from irony, tragedy, and melancholic inertia in the face of totalitarian suffocation.
A modern investiture: National sovereignty versus international war -- Heresies: Liberal(-Marxist) and Christian ethics of war -- Theo-logics of mediation.
Includes bibliographical references (pages 227-245) and index.